EXERGETIC ANALYSIS OF A MONOHYDRATE ABSORBER IN THE PRODUCTION OF SULFURIC ACID WITH A HEAT RECOVERY ABSORPTION SYSTEM - Aksenchik, Konstantin V.; Andreev, Aleksandr S.; Dracheva, Lubov’ N. (ChemChemTech, 2025)
An urgent problem of utilization of secondary energy resources with low temperature potential in sulfuric acid industries operating by the method of double contacting and double absorption is presented in the article. It is shown that the main low-potential heat in sulfuric acid production is the heat of heated sulfuric acid. The acid is heated during the absorption process as a result of the chemical interaction of sulfur trioxide with water to form sulfuric acid. In classical schemes, this heat is not used and is completely lost to the environment due to the organization of cooling of circulating sulfuric acid with recycled water, which in turn is cooled in a cooling tower. A brief analysis of the methods of heat absorption utilization known in the world practice is presented in the paper, their features are noted. To assess the level of energy technology of the object of study, the exergetic method was used in the work. A mathematical model has been developed that allows quantifying the exergetic balance of a monohydrate absorber. The exergetic efficiency coefficient of a monohydrate absorber was adopted as a criterion for comparing the energy-technological efficiency of the absorption process according to the classical scheme and according to the scheme with the utilization of absorption heat. As a result of the simulation, it was found that the exergetic efficiency increases with the introduction of an absorption heat recovery system, and exergy losses decrease. For a more complete assessment of the energy efficiency of the introduction of an absorption heat recovery system into classical sulfuric acid production schemes using the double contacting and double absorption method, the developed model can be supplemented with an exergetic balance of a heat exchange device for heat absorption utilization, which may be the subject of further research. For citation: Aksenchik K.V., Andreev A.S., Dracheva L.N. Exergetic analysis of a monohydrate absorber in the production of sulfuric acid with a heat recovery absorption system. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2025. V. 68. N 5. P. 64-71. DOI: 10.6060/ivkkt.20256805.1f.